(untitled) (World Science, 2021)
Ecosystem management is the process of maintaining basic agro-ecological services and restoring natural resources, it meets the modern challenges of the younger generation – their socio-economic, political and cultural needs. The main condition for sustainability in ecosystem management is the effective maintenance and social use of natural resources. This is a multilateral approach that requires significant changes in terms of natural processes and the human impact on the environment. Nowadays, when global problems are getting worse, it becomes more and more necessary to study the fundamental processes of the production of material and energy in nature. Attention should be paid to the growing influence of proper human activity on the planet’s biochemical cycle, the inappropriate impact of human activity can lead to a global ecological crisis. Sustainability of agroecosystems, optimal use of natural resources, protection from environmental pollution, stimulation of reproduction, etc.